Incidence and Risk Factors for Medical Complications and 30-Day End points After Carotid Artery Stenting. (January 2014) - Wang, Jun; Si, Yanfang; Li, Sheng; Cao, Xiangyu; Liu, Xinfeng; Du, Zhihua; Ge, Aili; Zhang, Alan; Li, Baomin
With the extensive use of carotid artery stenting (CAS) surgeries, scholars are paying more attention to the safety and efficiency of CAS. Our study aims to analyze the clinical efficiency, safety, and technical feasibility of CAS surgery in the treatment of carotid artery stenosis. A total of 379 cases of CAS were collected and retrospectively analyzed. The outcomes were summarized according to decrease in stenosis extent, incidence of early complications after procedure, 30-day end point events, and the follow-up data. Logistic regression was employed to analyze the correlations between risk factors and complications within 30 days and 30-day end points of stroke, myocardial infarctions (MIs), and mortality. The average extent of stenosis reduced from preoperative (81% ± 17%) to postoperative (26% ± 17%). In all, 53 patients had 72 medical complications, including 6 (1.58%) cerebral hemorrhage, 7 (1.85%) cerebral infarction, 5 (1.32%) transient ischemic attack (TIA), 5 (1.32%) heart failure, 10 (2.63%) symptomatic hypertension, 21 (5.54%) symptomatic hypotension, 10 (2.63%) symptomatic bradycardia, and 8 other complications; 15 patients had at least 2 complications. Advanced age, diabetes, and heart failure were associated with the high incidence of early complications ( P < .05). Asymptomatic stenosis (odds ratio [OR] = 0.39, 95% confidence interval [CI]: 0.131-1.131, P = .0426) and diabetes (OR = 3.38, 95% CI: 1.340-8.574, P = .0099) were correlated with the incidence of 30-day end point events. Diabetes and symptomatic stenosis are independent risk factors for 30-day end point events of CAS. Advanced age, hypertension, and vascular unstable plaque will increase the risk of postoperative complications.